2022
DOI: 10.1111/jog.15369
|View full text |Cite
|
Sign up to set email alerts
|

The outcomes of sequential embryo transfer in patients undergoing in vitro fertilization with frozen–thawed embryos: A retrospective study

Abstract: Aim: To explore whether sequential embryo transfer benefits patients with repeated implantation failure (RIF) undergoing frozen-thawed embryo transfer (FET) cycles. Methods: We included 311 patients with a history of RIF in this retrospective study. We did sequential transfers with a cleavage embryo on day 3 and a blastocyst on day 5 in 77 patients; blastocyst transfers with two blastocysts on day 5 in 80 patients; and cleavage embryo transfers with two cleavage embryos on day 3 in 154 patients. We compared cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…In the cycles following IVF, more mature follicles are formed due to the use of ovarian stimulating drugs, so the level of these hormones can be higher than the physiological state. This increase in level can cause concern about luteal phase disorders and uterine tissue changes (7). E2 first causes hyperplasia and hypertrophy of endometrial epithelial cells (9), but its role in the luteal phase is unclear (8).…”
Section: Introductionsupporting
confidence: 92%
See 3 more Smart Citations
“…In the cycles following IVF, more mature follicles are formed due to the use of ovarian stimulating drugs, so the level of these hormones can be higher than the physiological state. This increase in level can cause concern about luteal phase disorders and uterine tissue changes (7). E2 first causes hyperplasia and hypertrophy of endometrial epithelial cells (9), but its role in the luteal phase is unclear (8).…”
Section: Introductionsupporting
confidence: 92%
“…In the conducted studies, the harmful effect of high E2 on the receptivity of the endometrium has been proposed (4,5); however, in some studies, this negative effect has not been reported (6,7). The role of E2 in the follicular phase, including the proliferation of stroma and glandular epithelial vessels in the endometrial tissue, has been discussed (5,6).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The cryopreserved embryos are used for subsequent frozen embryo transfer (FET). The transfer protocol included sequential transfer, embryo transfer and blastocytes transfer [21]. It referred that patients were transferred 1-2 frozen embryos and/or blastocytes after ovulation 3 and/or 5 days, respectively.…”
Section: Fresh or Frozen Embryos Transfer And Pregnancy Con Rmationmentioning
confidence: 99%